Can post-eradication laboratory containment of wild polioviruses be achieved? - Dowdle Walter R.; Gary Howard E.; Sanders Raymond; Loon Anton M. van (The World Health Organization, 2002)
The purpose of containment is to prevent reintroduction of wild polioviruses from laboratories into polio-free communities. In order to achieve global commitment to laboratory containment the rationale should be clear and compelling; the biosafety levels should be justified by the risks; and the objectives should be realistic. Absolute containment can never be assured. Questions of intentional or unintentional non-compliance can never be wholly eliminated. Effective laboratory containment is, however, a realistic goal. Prevention of virus transmission through contaminated laboratory materials is addressed by WHO standards for biosafety. The principal challenge is to prevent transmission through unrecognized infectious laboratory workers. Such transmission is possible only if the following conditions occur: infectious and potentially infectious materials carrying wild poliovirus are present in the laboratory concerned; a laboratory operation exposes a worker to poliovirus; a worker is susceptible to an infection that results in the shedding of poliovirus; and the community is susceptible to poliovirus infections. At present it is difficult to envisage the elimination of any of these conditions. However, the risks of the first three can be greatly reduced so as to create a formidable barrier against poliovirus transmission to the community. Final biosafety recommendations must await post-eradication immunization policies adopted by the international community.